Identifying HLA DRB1-DQB1 alleles associated with Chlamydia trachomatis infection and in silico prediction of potentially-related peptides - Pedraza, Leidy (Sci Rep, 2021)
HLA class II (HLA-II) genes’ polymorphism influences the immune response to Chlamydia trachomatis (Ct), it is considered a sexually transmitted infection. However, associations between HLA-II alleles and Ct-infection have been little explored in humans; this study was thus aimed at determining HLA-DRB1-DQB1 alleles/haplotypes’ effect on Ct-infection outcome in a cohort of Colombian women. Cervical sample DNA was used as template for detecting Ct by PCR and typing HLA-DRB1-DQB1 alleles/haplotypes by Illumina MiSeq sequencing. Survival models were adjusted for identifying the alleles/haplotypes’ effect on Ct-outcome; bioinformatics tools were used for predicting secreted bacterial protein T- and B-cell epitopes. Sixteen HLA-DRB1 alleles having a significant effect on Ct-outcome were identified in the 262 women analysed. DRB1*08:02:01G and DRB1*12:01:01G were related to infection-promoting events. Only the DQB1*05:03:01G allele related to clearance/persistence events was found for HLA-DQB1. HLA-DRB1 allele homozygous women were associated with events having a lower probability of clearance and/or early occurrence of persistence. Twenty-seven peptides predicted in silico were associated with protective immunity against Ct; outer membrane and polymorphic membrane protein-derived peptides had regions having dual potential for being T- or B-cell epitopes. This article describes HLA-DRB1-DQB1 alleles/haplotypes related to Ct-infection resolution and the peptides predicted in silico which might probably be involved in host immune response. The data provides base information for developing future studies leading to the development of effective prevention measures against Ct-infection.